The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.joc.9b00120
|View full text |Cite
|
Sign up to set email alerts
|

External Oxidant-Dependent Reactivity Switch in Copper-Mediated Intramolecular Carboamination of Alkynes: Access to a Different Class of Fluorescent Ionic Nitrogen-Doped Polycyclic Aromatic Hydrocarbons

Abstract: An interesting case of external oxidant-controlled reactivity switch leading to a divergent set of ionic nitrogen-doped polycyclic aromatic hydrocarbons (N-doped PAHs), is presented here, which is quite unrecognized in copper-mediated reactions. In the current scenario, from the same pyridino-alkyne substrates, the use of the external oxidant PhI­(OAc)2, in combination with Cu­(OTf)2, gave N-doped spiro-PAHs via a dearomative 1,2-carboamination process; whereas, without the use of oxidant, an alkyne/azadiene [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…It was later found that the outcome of the reaction depends on the oxidant; in particular, the use of a hypervalent iodine reagent led to spirocyclized products. 516 …”
Section: Nonbenzenoid Fusionmentioning
confidence: 99%
“…It was later found that the outcome of the reaction depends on the oxidant; in particular, the use of a hypervalent iodine reagent led to spirocyclized products. 516 …”
Section: Nonbenzenoid Fusionmentioning
confidence: 99%
“…Interestingly, the use of oxidant PhI(OAc) 2 as an additive offered a completely different product 111 ( Scheme 63 ). 76 The reaction offered access to variously substituted PAHs. Interestingly, aliphatic alkynes did not produce the desired 111, but 110 was obtained in good yield.…”
Section: Intramolecular Carboaminationmentioning
confidence: 99%
“…). [41] Thus, based on an "optimization-on-observation" approach, an oxidant-controlled reactivity switch has been achieved on these pyridinoalkyne cores. To the best of our knowledge, this reaction represents the first example of intramolecular dearomative 1,2carboamination of alkynes utilizing oxidative copper chemistry.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…In our continuing research on realizing 1,2-aminofunctionalization reactions of pyridino-alkynes, a diverse synthetic potential of these cores was discovered based on their reactivity switch in presence of different metal catalysts. While working on the optimization of our initial project regarding Cu(OTf) 2mediated 1,2-carboamination reaction of 2-phenyl-6-(2-alkynylphenyl)pyridine skeletons (41) for the synthesis of PAHs 42 (Scheme 13), [39] formation of pyrido-isoquinoline salts 64 was encountered during the screening of silver catalysts. An AgOTf-mediated hydroamination reaction of 63 has successfully led to access 64 (Scheme 22).…”
Section: 2-hydroamination Reactionmentioning
confidence: 99%
See 1 more Smart Citation